Identification of a novel BET bromodomain inhibitor‐sensitive, gene regulatory circuit that controls Rituximab response and tumour growth in aggressive lymphoid cancers. Issue 8 (4th July 2013) - Emadali, Anouk; Rousseaux, Sophie; Bruder‐Costa, Juliana; Rome, Claire; Duley, Samuel; Hamaidia, Sieme; Betton, Patricia; Debernardi, Alexandra; Leroux, Dominique; Bernay, Benoit; Kieffer‐Jaquinod, Sylvie; Combes, Florence; et al.
<x xml:space="preserve">Abstract</x> Immuno‐chemotherapy elicit high response rates in B‐cell non‐Hodgkin lymphoma but heterogeneity in response duration is observed, with some patients achieving cure and others showing refractory disease or relapse. Using a transcriptome‐powered targeted proteomics screen, we discovered a gene regulatory circuit involving the nuclear factor CYCLON which characterizes aggressive disease and resistance to the anti‐CD20 monoclonal antibody, Rituximab, in high‐risk B‐cell lymphoma. CYCLON knockdown was found to inhibit the aggressivity of MYC‐overexpressing tumours in mice and to modulate gene expression programs of biological relevance to lymphoma. Furthermore, CYCLON knockdown increased the sensitivity of human lymphoma B cells to Rituximab in vitro and in vivo. Strikingly, this effect could be mimicked by in vitro treatment of lymphoma B cells with a small molecule inhibitor for BET bromodomain proteins (JQ1). In summary, this work has identified CYCLON as a new MYC cooperating factor that autonomously drives aggressive tumour growth and Rituximab resistance in lymphoma. This resistance mechanism is amenable to next‐generation epigenetic therapy by BET bromodomain inhibition, thereby providing a new combination therapy rationale for high‐risk lymphoma.